2017
DOI: 10.1063/1.4990693
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing dynamical features of water inside protein hydration layer: Distribution reveals what is hidden behind the average

Abstract: Since the pioneering works of Pethig, Grant and Wüthrich on protein hydration layer, many studies have been devoted to find out if there are any "general and universal" characteristic features that can distinguish water molecules inside the protein hydration layer from bulk. Given that the surface itself varies from protein to protein, and that each surface facing the water is heterogeneous, search for universal features has been elusive.Here, we perform atomistic molecular dynamics simulation in order to prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 76 publications
(108 reference statements)
5
64
0
Order By: Relevance
“…The rotational motion of water on biological surface is slowed down compared to that in the bulk. 30,[70][71][72] We find a similar slowing down for the water molecules inside cavity. In addition, we observed that the rotational motion inside protein cavity is highly anisotropic with the rotation of the dipole moment vector being the slowest among all the three orthogonal vectors (Fig.…”
Section: Rotational Anisotropysupporting
confidence: 67%
“…The rotational motion of water on biological surface is slowed down compared to that in the bulk. 30,[70][71][72] We find a similar slowing down for the water molecules inside cavity. In addition, we observed that the rotational motion inside protein cavity is highly anisotropic with the rotation of the dipole moment vector being the slowest among all the three orthogonal vectors (Fig.…”
Section: Rotational Anisotropysupporting
confidence: 67%
“…For example, large hydrophobic patches at protein surfaces can induce large fluctuations in nearby water density (18), strengthening and accelerating protein−protein association (19). More generally, spatial heterogeneity in hydration shell dynamics, influenced by local geometry and chemical patterning, is a hallmark of proteins of all sizes and functions (20,21). Recent experimental measurements have also shown that such heterogeneity is unique to the folded, structured protein and does not appear in corresponding peptide fragments or intrinsically disordered proteins, suggesting the importance of spatially organized heterogeneity in the well-defined folded structure (5).…”
mentioning
confidence: 99%
“…The energetic distribution across the different types of biological water indicates a larger specific heat for the hydration layer compared to bulk, and this in turn may help stabilize protein structures by minimizing temperature fluctuations in the protein-associated water. [68] All ultrafast physicochemical phenomena investigated to elucidate the dynamics and energetics of biological water, such as solvation dynamics, excited-state proton transfer, and depolarization dynamics, depend on different aspects of the hydration environment surrounding a fluorophore, including the local polarity, H-bond network, and micro-viscosity of the medium. The most important aspect that should be considered, while designing experiments to understand the dynamics of biological water, is the need to minimize any perturbation of the biological structures caused by the incorporation of the probe into the system.…”
Section: Discussionmentioning
confidence: 99%
“…Using several proteins that were chosen for the diversity of their structure, function, and helix-sheet ratio, Mukherjee et al showed how the broad distribution of residence times and rotation relaxation times of water molecules within the protein hydration layer is responsible for the non-exponential nature of the dielectric response often observed for biological water. [68][69][70][71] Water molecules bound to peptide backbones around hydrophobic residues can be more mobile than bulk water molecules. In contrast, those bound to charged amino acid groups show substantial retardation of the associated dynamics.…”
Section: Computational Studiesmentioning
confidence: 99%